2020
DOI: 10.34297/ajbsr.2020.07.001160
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Budding in Oral Cavity Cancer

Abstract: This work is licensed under Creative Commons Attribution 4.0 License AJBSR.MS.ID.001160.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…As a result, they determined that TB in the TSCC was a biological marker that predicted a poor prognosis. 18 The findings of our study (P = 0.59, not significant) (Table 3), demonstrated that there is no relationship between the presence or absence of TB and patient survival rates, which is in accordance with previous studies by Joshi et al (2020) 16 and Fernando Candanedo-Gonzalez et al (2020). 18 Nandita et al (2016), 24 investigated the contribution of TB to the diagnosis of OSCC.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As a result, they determined that TB in the TSCC was a biological marker that predicted a poor prognosis. 18 The findings of our study (P = 0.59, not significant) (Table 3), demonstrated that there is no relationship between the presence or absence of TB and patient survival rates, which is in accordance with previous studies by Joshi et al (2020) 16 and Fernando Candanedo-Gonzalez et al (2020). 18 Nandita et al (2016), 24 investigated the contribution of TB to the diagnosis of OSCC.…”
Section: Discussionsupporting
confidence: 93%
“…18 The findings of our study (P = 0.59, not significant) (Table 3), demonstrated that there is no relationship between the presence or absence of TB and patient survival rates, which is in accordance with previous studies by Joshi et al (2020) 16 and Fernando Candanedo-Gonzalez et al (2020). 18 Nandita et al (2016), 24 investigated the contribution of TB to the diagnosis of OSCC. For this investigation, 30 histological samples of OSCC with a biopsy-proven diagnosis were chosen.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations